ENHANCING MULTILINGUALISM IN BASIC EDUCATION: THE INTEGRATION OF ISIZULU INTO TECHNOLOGY IN KWAZULU-NATAL - Wilson, Strydom M (Global Research Journal of Management and Social Sciences (GRJMSS), 2022)
The marginalization of indigenous African languages in the South African education system has been a persistent issue despite legislative frameworks aimed at promoting multilingualism and language rights. This paper explores the integration of isiZulu into information and communication technology (ICT) in the basic education sector in KwaZulu-Natal as a potential solution to elevate the status of indigenous African languages. Drawing on the language-as-a-resource position, this paper discusses the benefits of integrating isiZulu into technology, including enhancing learning and addressing the low performance of South African schools. However, the implementation of multilingual language policies remains a challenge, leading to obstacles in integrating indigenous African languages into ICT. To address this, the paper proposes pedagogical training of teachers and the use of relevant resources tailored to subject teaching contexts. The paper concludes that the integration of indigenous African languages into ICT has the potential to positively fast-track efforts towards promoting these languages as a medium of instruction